The Pegasus Quest : The Kingdom of Wrenly #10 - Quinn, Jordan; McPhillips, Robert (New York : Little Simon, 2016)
"As Lucas and Clara set out to investigate some mysterious happenings in Wrenly, they discover a young horse with wings that is lost and in danger"--
Keywords: Animals, Mythical -- Fiction; Princes -- Fiction; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General